Acid-treated SWCNT/polyurethane nanoweb as a stretchable and transparent Conductor - Kim, Tae Ann; Lee, Sang-Soo; Kim, Heesuk; Park, Min (ROYAL SOC CHEMISTRY, 2012)
To obtain carbon-nanotube (CNT) conductors with high conductance and transmittance, well-connected conducting paths must be formed with a relatively small number of CNTs. In this study, we employed electrospun polyurethane (PU) nanofibers to guide the deposition of CNTs at desired locations, which makes it possible to acquire high conductivity at low concentrations of CNTs. PU has an affinity for CNTs and inherently elastic characteristics; thus, it can be applied as a stretchable scaffold for CNT deposition. A sample fabricated by nine dipping-and-washing cycles in acid-treated single-walled CNT (a-SWCNT) solution and distilled water, followed by doping, exhibited a sheet resistance of 424 Omega sq(-1) at 63%T. When we measured the resistance of a-SWCNT/PU conductors under a wide range of strains (up to 100%), their change in resistance was reduced as more stretching/releasing cycles were applied. In addition, these variations in resistance according to the number of stretching cycles could be significantly reduced when dipping and doping processes were performed using a pre-stretched PU nanoweb. After more than six stretching cycles, the resistance under a tensile strain of up to 100% remained nearly stable at a value of 8.15 k Omega. Our results demonstrate an effective way of preparing a transparent and stretchable conductor with stable performance during repetitive stretching and releasing.
Keywords: WALLED CARBON NANOTUBES; THIN-FILMS; ELASTIC CONDUCTORS; ELECTRODES; SUPERCAPACITORS; OPTOELECTRONICS; PERFORMANCE; FABRICATION; PRESSURE; SENSORS